Plan de marketing que mejore el habito alimenticio mediante el consumo de carne de codorniz en cinco frigoríficos en el cantón Durán en el año 2016 - Álvarez Lacera, Angie Tamara (2015)
This thesis project aims to develop a marketing plan to improve the eating habits by eating quail meat in five refrigerators in the canton Duran in 2016, within the present research marketing strategies were raised to help us to introduce and market our product by publicizing the benefits and nutrients it has, to encourage their use by giving them a healthy option when feeding. It is noteworthy that food is the primary activity of human beings, which is why it is considered that every human being should have a good diet because it is one that fully meets the needs of the person. While the quail meat is not known nor consumed by the inhabitants of Duran but in other countries it is considered one of the birds most nutritional value and its consumption is common among nutrients include vitamins and minerals such as the magnesium and iron…..